2016
DOI: 10.1002/ecy.1603
|View full text |Cite
|
Sign up to set email alerts
|

Climate change increases the production of female hatchlings at a northern sea turtle rookery

Abstract: Abstract. The most recent climate change projections show a global increase in temperatures, along with major adjustments to precipitation, throughout the 21st century. Species exhibiting temperature-dependent sex determination are highly susceptible to such changes since the incubation environment influences critical offspring characteristics such as survival and sex ratio. Here we show that the mean incubation duration of loggerhead sea turtle (Caretta caretta) nests from a high-density nesting beach on Bald… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 33 publications
(73 reference statements)
2
15
0
Order By: Relevance
“…Results from this study predict a significant increase in the proportion of female hatchlings pro-duced in Qatar in the 21 st century, an important nesting ground in the Gulf (Tayab & Quiton 2003, Pilcher et al 2014a, Chatting et al 2018. These results support other predictive studies forecasting significant feminization of primary sex ratios in marine turtle species around the world (Fuentes et al 2009, Laloë et al 2016, Reneker & Kamel 2016, Monsinjon et al 2019b, Patrício et al 2019). An almost 'complete feminization' of green turtles Chelonia mydas in the northern Great Barrier Reef has been predicted (Jensen et al 2018, p. 154).…”
Section: Discussionsupporting
confidence: 89%
“…Results from this study predict a significant increase in the proportion of female hatchlings pro-duced in Qatar in the 21 st century, an important nesting ground in the Gulf (Tayab & Quiton 2003, Pilcher et al 2014a, Chatting et al 2018. These results support other predictive studies forecasting significant feminization of primary sex ratios in marine turtle species around the world (Fuentes et al 2009, Laloë et al 2016, Reneker & Kamel 2016, Monsinjon et al 2019b, Patrício et al 2019). An almost 'complete feminization' of green turtles Chelonia mydas in the northern Great Barrier Reef has been predicted (Jensen et al 2018, p. 154).…”
Section: Discussionsupporting
confidence: 89%
“…Relatively few studies have inferred the sex ratio of marine turtle populations; however, the majority of these report female‐biased primary sex ratios which are expected to skew further with climate warming (Fuentes et al., ; Hawkes et al., ; Katselidis, Schofield, Stamou, Dimopoulos, & Pantis, ; Patino‐Martinez, Marco, Quiñones, & Hawkes, ; Reneker & Kamel, ), and incubation temperatures above a certain threshold are expected to reduce clutch survival (Hays et al., ; Santidrián Tomillo et al., ), and hatchling locomotor ability (Booth & Evans, ; Fuentes, Hamann, & Limpus, ). Significant losses of 8%–65% of nesting habitat are predicted for several sea turtle rookeries, under climate change scenarios of median severity (Baker, Littnan, & Johnston, ; Fish et al., , ; Fuentes, Limpus, Hamann, & Dawson, ; Katselidis, Schofield, Stamou, Dimopoulos, & Pantis, ).…”
Section: Introductionmentioning
confidence: 99%
“…Whether these long‐lived species have the potential to adapt to global climate change via shifts in nesting phenology or nest‐site selection behaviors is still unknown (Hawkes et al 2007, Schwanz and Janzen 2008, Refsnider et al 2013, Reneker and Kamel 2016 b ). However, we have shown that beach nourishment can cause significant changes to the thermal profile of loggerhead nesting beaches and we support a directed effort to incorporate these impacts into species assessments.…”
Section: Discussionmentioning
confidence: 99%